KEANEKARAGAMAN JENIS KUPU-KUPU BERDASARKAN TIPE TUTUPAN LAHAN DAN WAKTU AKTIFNYA DI KAWASAN PENYANGGA TANGKAHAN TAMAN NASIONAL GUNUNG LEUSER - Irni, Julaili; Masy'ud, Burhanuddin; Haneda, Noor Farikhah (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Butterfly is one of insect that comes from Lepidotera and has a very important role in maintaining ecosystem. Tangkahan is a Gunung Leuser National Park buffer zone that has been defined as a tourism area and make butterfly as one of tourism object. This study aims to identify and analyze the diversity of butterfly by active time (morning and afternoon) as well as the diversity of food plant and host plant in three types of buffer zones area. This research was conducted in December 2015 to February 2016 in Tangkahan, Gunung Leuser National Park buffer zone. The data was collected on three types of land cover that sattlement, river and forest.The observation of butterfly, food plant and host plant diversity were done using transect Pollard Method. Based on the study 5 family of butterflies were recorded with number of species as many as 61 species and 1.213 individuals. Food plants species were found as many as 48 species, while hosts plant were 27 species, and consisted of covercrop, sapling and poles. The highest of butterfly and food plant diversity index were recorded in the settlement for 3,43 and 2,75, the highest of host plant diversity index was recorded in the forest for 2,06. Keyword: butterfly, food plant, host plant